2009
DOI: 10.1088/0004-637x/702/2/1413
|View full text |Cite
|
Sign up to set email alerts
|

Inflating and Deflating Hot Jupiters: Coupled Tidal and Thermal Evolution of Known Transiting Planets

Abstract: We examine the radius evolution of close-in giant planets with a planet evolution model that couples the orbital-tidal and thermal evolution. For 45 transiting systems, we compute a large grid of cooling/contraction paths forward in time, starting from a large phase space of initial semi-major axes and eccentricities. Given observational constraints at the current time for a given planet (semi-major axis, eccentricity, and system age) we find possible evolutionary paths that match these constraints, and compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
194
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(207 citation statements)
references
References 91 publications
13
194
0
Order By: Relevance
“…Similarly, we estimate 12 a mass loss rate of about 8 3 10 6 g s 21 , which is the lowest one among the known transiting gas giants; escape processes have therefore not affected the planet significantly since its origin. That CoRoT-9b has a much larger periastron distance than any other known transiting exoplanet also strongly constrains its composition, independently of hypotheses 11,13 on possible missing energy sources and associated radius inflation: An evolutionary model of CoRoT-9b (Fig. 3) shows a good match to the observed radius between 0 and 20 Earth masses of heavy elements, comparable to the composition of giant planets in our Solar System 6 .…”
mentioning
confidence: 68%
“…Similarly, we estimate 12 a mass loss rate of about 8 3 10 6 g s 21 , which is the lowest one among the known transiting gas giants; escape processes have therefore not affected the planet significantly since its origin. That CoRoT-9b has a much larger periastron distance than any other known transiting exoplanet also strongly constrains its composition, independently of hypotheses 11,13 on possible missing energy sources and associated radius inflation: An evolutionary model of CoRoT-9b (Fig. 3) shows a good match to the observed radius between 0 and 20 Earth masses of heavy elements, comparable to the composition of giant planets in our Solar System 6 .…”
mentioning
confidence: 68%
“…4 and 5, we compare the constant time-lag model with the constant Q model used by various authors. In order to allow a direct and immediate comparison with these studies, we will choose the values of the couple (Δt p , Δt ) from the relations (k 2 Δt p = 3 2n obs Q p , k 2 Δt = 3 2n obs Q ), where (Q p , Q ) are the constant normalized quality factors used by Miller et al (2009). This ensures that the effective tidal dissipation function is the same in both calculations for a given planet with its measured orbital parameters.…”
Section: Relationship Between the Time Lag δT And The Quality Factor (Q)mentioning
confidence: 99%
“…Following Bodenheimer et al (2001) and Gu et al (2003), attempts have been made to explain the observed large radius of some transiting close-in gas giant exoplanets -the so-called "Hot Jupiters" -by means of tidal heating (Jackson et al 2008;Miller et al 2009;). All these models, however, use tidal models truncated to a low (2nd) order in eccentricity, in spite of initial eccentricities, as determined from the tidal evolution calculations, which can be as large as e = 0.8!…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism, in turn, might be responsible for heating up the planet's interior and bloating its radius in consequence (Miller et al 2009). The orbit of WASP-12 b is expected to be circularised on short timescales if the tidal dissipation A&A 551, A108 (2013) Notes.…”
Section: Introductionmentioning
confidence: 99%